Phenomenon of Knowledge Management Implementation in an Organization - Yuliyanto, H (KnE Social Sciences, 2018)
Knowledge management (KM) is a combination of people, processes and technology to manage the knowledge conducted continuously that produces creativity and innovations that help the company’s strategy in the global competition. This article discusses the concept and implementation of knowledge management within the company. Besides, it also discusses the relationship between the environmental organizations and the individual’s perception of the use of knowledge. It was found that the cognitive aspects of knowledge management and enterprise environments have insignificant influence on individuals to gain new knowledge. However, the cognitive aspects of knowledge management, the company and the individual activities to gain knowledge provide a significant influence on the use of knowledge to get the job done. Keywords: knowledge management, cognitive, behavior, contextual